Perbanyakan Tanaman Anggur Ninel (Vitis vinifera L) dengan Metode Stek Sambung pada Spesies Batang Bawah dan Media Tanam yang Berbeda - Historiawati (Indoensia), Historiawati; Iftitah (Indoensia), Siti Nurul; Sofwan (Indoensia), Nurus (Universitas Tidar, 2023)
Grafted cutting is a method for vegetative Ninel vine propagation. The purpose of thisstudy was to ascertain the impact of several grapevine rootstock species and planting media types on the development of Ninel grape seeds propagated through grafted cutting. The study was conducted in Kebonrejo village, Salaman district, Magelang regency (290 m asl) from April 2 to May 24, 2022, using a randomized complete block design (RCBD) consist of 2 treatment factors with 3 blocks. The rootstock species of grapevines, such us Vitis vinifera, Vitis labrusca, and Vitis riparia are the first factor. Planting media types classified as second factor include blends of topsoil + husk charcoal, topsoil + cocopeat, and topsoil + sand. The datas were anylized by Anova and continued with the Least Significant Difference (LSD) test and Duncan's Multiple Range Test (DMRT). The findings demonstrated that the grafted cutting method with rootstock from the Vitis riparia species on the scion of Vitis vinifera of the Ninel variety had the maximum yield in terms of shoot length, shoot diameter, leaf area and grafting success. Topsoil + husk charcoal and topsoil + sand were the types of planting medium that had the greatest effectiveness at grafted cutting.Keywords : planting medium, rootstock species, grafted cutting, Ninel vine